2012
DOI: 10.7763/ijapm.2012.v2.54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison with Low-Velocity Impact and Quasi-staticIndentation Testing of Foam Core Sandwich Composites

Abstract: Abstract-The need for quasi-static indentation test method for modeling low-velocity foreign object impact events would prove to be very beneficial to researchers. In order to examine whether it is feasible, series of quasi-static indentation and low-velocity impact tests were carried out and compared. An analysis of the relationships between impact energy (or quasi-static indentation force) and damage area, dent depth indicates clearly that dent depth was selected as the damage parameter to set up damage rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…(8) The crater produced by the crack propagation and chipping in brittle material is hemispherical in shape. (9) Based on the low velocity impact characteristics reported in the literature [28,40], strain hardening and the associated effects are neglected. The negative effects of pre-existing flaws of work material, the effect of erodent rotation, etc., are also not considered at present.…”
Section: Assumptionsmentioning
confidence: 99%
“…(8) The crater produced by the crack propagation and chipping in brittle material is hemispherical in shape. (9) Based on the low velocity impact characteristics reported in the literature [28,40], strain hardening and the associated effects are neglected. The negative effects of pre-existing flaws of work material, the effect of erodent rotation, etc., are also not considered at present.…”
Section: Assumptionsmentioning
confidence: 99%
“…The Newmark's implicit time integration scheme is used in the present paper for solving transient dynamic equations, despite experiments have shown that low-velocity impact studies could be carried out also in static form (see, Li et al (2012)). One practical reason for carrying out a transient analysis is that dynamic effects can be captured progressively increasing the impactor velocity, thus a unique scheme can be used for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Research issues in the scope of dynamic loads by means of concentrated force in composite materials and interpretation of the effects of their impacts are extremely complex. Therefore, the attempts are made to predict the resistance to dynamic loads by means of concentrated force using statistical research methods (Li et al, 2012;Nettles and Douglas, 2000;Sjoblom et al, 1998;Lagace et al, 1993;Lber, 1983;Dong et al, 2015;Kwon and Sankar, 1993). From available studies, it appears that it is possible to find an estimated assessment of the resistance to impacts on the basis of analogical static loads (Nettles and Douglas, 2000;Dong et al, 2015;Kwon and Sankar, 1993).…”
Section: Introductionmentioning
confidence: 99%